Respuesta :
Mult all 4 terms by 2 to elilminate numerical fractions:
n-4 - 3(2) = 3(2) - 4n - 6
Group like terms together: -4 - 6 = 6 - 4n - 6 - n, or -4 - 6 = 6 - 5n - 6
Simplifying, -10 = -5n, and thus n = 2 (answer)
n-4 - 3(2) = 3(2) - 4n - 6
Group like terms together: -4 - 6 = 6 - 4n - 6 - n, or -4 - 6 = 6 - 5n - 6
Simplifying, -10 = -5n, and thus n = 2 (answer)
Answer:
n=2
Step-by-step explanation:
The given equation is
[tex]\frac{1}{2}(n-4)-3=3-(2n+3)[/tex]
Distribute 1/2 and minus sign over the parenthesis
[tex]\frac{1}{2}n-2-3=3-2n-3[/tex]
Group the like terms
[tex]\frac{1}{2}n+2n=3-3+2+3[/tex]
Combine the like terms
[tex]\frac{5}{2}n=5[/tex]
Multiply both sides by 2/5
[tex]n=2[/tex]
The value of n = 2